Antonimija enako motiviranih paremioloških enot - Meterc, Matej (Slavistična revija, 2013)
The article examines the ways in which linguistic means used for expressing the opposite meaning are realized in phraseology, i.e., in pairs of phraseological units with identical motivation. It focuses on the questions of opposite meaning in paremiology and of the existence of paremiological antonymous nests. Based on examples from Slovak and Slovene, it attempts to determine when (if at all) it is possible to speak of antonymous nests and what the specifics of the antonymous paremiological units with identical motivation are. The article is based on the results of a demographic study of the knowledge of Slovene proverbs as part of doctoral research and on the data from the language corpus Gigafida.
Keywords: anti-proverbs; antonimija; antonymical nests; antonymy; leksikologija; lexicology; paremiologija; paremiology; pregovori; Slovak langauge; slovaščina; Slovene; Slovenian langauge; slovenščina; wellerisms